The Determinants of Purchasing Decision for Alwahida Herbal Products in Padang Lawas District - Rambe, Sarwedi; Harahap , Darwis; Utari Evy Cahyani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The sales of HPAI-HNI products in Padang Lawas Regency fluctuate due to limited marketing, resulting in low consumer awareness. Ineffective promotion, high prices, and inadequate attention to halal labels necessitate a study on purchasing decisions. This research aims to analyze how product knowledge, promotion, price, and halal labels influence purchasing decisions. Consumer behavior theory guides the study, emphasizing preferences and needs in decision-making. Marketing theory informs strategies to meet customer needs, while purchasing decision theory focuses on the decision-making process. These theories are integrated with variables of product knowledge, promotion, price, and halal labels. Using quantitative methods, 264 respondents from three distributors are sampled using stratified random sampling. Data is analyzed using SEM-PLS method with WarpPLS 8.0 application, revealing positive impacts of product knowledge, promotion, price, and halal labels on purchasing decisions. The research findings indicate that product knowledge, promotion, price, and halal labels have a positive impact on the purchasing decisions for HPAI-HNI products in Padang Lawas Regency. The significance of an educational marketing approach, including workshops, local promotional investments, price adjustments, and clear halal certification, is highlighted to attract consumers and build trust in the products. Therefore, it is essential to establish partnerships with local governments or community organizations to enhance the accessibility of HPAI-HNI products and develop health and beauty products or variants that better align with the market needs and preferences in Padang Lawas Regency.